PERAN DIGITALISASI DAN MANAJEMEN PEMASARAN DALAM MENINGKATKAN KETAHANAN INDUSTRI MIKRO DAN KECIL (IMK) DENGAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL MEDIASI - Putri, Fenina Berliana; Sofyan, Ade; Maulidah, Siti Aisyah (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The acceleration of digital transformation has reshaped the competitive landscape of micro and small industries (IMK). Despite this shift, IMK in Indonesia, particularly within the leather, leather goods, and footwear subsector, continue to face significant challenges in maintaining business resilience due to resource limitations and intense competition from imported products. This study investigates the influence of digitalization and marketing management on IMK resilience, with competitive advantage positioned as a mediating variable. A quantitative approach with a descriptive verificative design was applied, involving 202 respondents selected through the Isaac and Michael formula. Data were analyzed using Structural Equation Modeling with SmartPLS. The findings reveal that digitalization and marketing management significantly enhance both competitive advantage and business resilience. Moreover, competitive advantage serves as a mediating mechanism that links digitalization and marketing management to resilience, emphasizing the pivotal role of differentiation, cost leadership, and service responsiveness in sustaining IMK performance. Theoretically, this study introduces novelty by positioning competitive advantage not merely as an outcome but as a central mediator that bridges digital strategies and resilience, a perspective that remains underexplored in prior research. Practically, the study provides valuable insights for policymakers and entrepreneurs in designing adaptive strategies that strengthen the competitiveness and sustainability of IMK in the digital era. Keywords: Digitalization, Marketing Management, Competitive Advantage, Business Resilience, micro and small industries